Product Development. User-centred product development and design in an industrial company - Höglund, Anna (My University, 2012)
User-centred product development is a process the goals of which are to create a product that satisfies the needs of the user. Instead of only concentrating on technical sides of the product, the focus is mostly on fulfilling customer requirements and wishes. The structure of the entire process encourages the activities such as market research, investigation of the nature of the customers, their needs and preferences. The aim of this research was to investigate user-centred product development from both theoretical and practical perspectives and to find out at which rate the practice corresponds to the theory. The product development process of an industrial company was investigated. As an example ABB Finland Oy Motors and Generators was chosen. The company’s product development process was introduced and compared to the theoretical model known as the stage-gate system. Another aim of this research was to investigate open innovation and present its principles in product development. Open source was presented as an example of open innovation. Finally, the goal was to find out the ways to improve the process of user-centred product development in an industrial company. The results of the investigation have shown that the challenges presented by the theory are taking place in the real world. Changing market, environment and customer tastes, existence of multiple choices, growing time pressure and pressure to succeed – all these factors strengthen the importance of customer prioritisation. The study showed that the company can succeed by asking questions, using users as a source of a new product idea, having a user needs-and-wants study and further developing the process structure.
Keywords: user-centred development; stage-gate system; open innovation; open source; customer needs; fi=Tuotantotalous|en=Industrial Management|